Proceedings of the Second International Conference on Theoretical, Applied and Experimental Mechanics - Gdoutos, Emmanuel E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the proceedings of the 2nd International Conference on Theoretical, Applied and Experimental Mechanics that was held in Corfu, Greece, June 23-26, 2019. It presents papers focusing on all aspects of theoretical, applied and experimental mechanics, including biomechanics, composite materials, computational mechanics, constitutive modeling of materials, dynamics, elasticity, experimental mechanics, fracture, mechanical properties of materials, micromechanics, nanomechanics, plasticity, stress analysis, structures, wave propagation. The papers update the latest research in their field, carried out since the last conference in 2018. This book is suitable for engineers, students and researchers who want to obtain an up-to-date view of the recent advances in the area of mechanics.
-- Studying of influence of the material anisotropy on the limit state of an orthotropic plate weakened by a periodic system of collinear cracks under biaxial loading, by Olga Bogdanova -- The Boundary-Element Approach to Modeling the Dynamics of Poroelastic Bodies, by Leonid Igumnov, Svetlana Litvinchuk, Aleksandr Ipatov and Tatiana Iuzhina -- Modeling Surface Waves on a Partially Saturated Poroelastic Half-Space, by Leonid Igumnov, Svetlana Litvinchuk, Andrey Petrov and Igor Vorobtsov -- Symposium on: "Elastostatic and Elastodynamic Problems for Thermosensitive and Nonhomogeneous Solids", by Roman Kushnir -- Residual Strength and Reliability of Corroded Pipelines - Monte-Carlo Approach for Consideration of Spatially Nonuniform Material Properties, by Alexey Milenin, Elena Velikoivanenko, Galina Rozynka and Nina Pivtorak -- Actual Problems of Structural Integrity Assessment of WWER-1000 Pressure Vessel Internals, by Makhnenko O.V., Kandala S.M. -- Vibration of Titanium Blades of Turbomachines for Nuclear Power Plants with Erosive Damage, by Yurii Vorobiov, Oleg Makhnenko, Nataliia Ovcharova, Anton Olkhovskyi -- Influence of Residual Stresses in the Cladding Zones of RPV WWER-1000 on Integrity Assessment, by Oleh Makhnenko and Elena Kostenevich -- Symposium on: "Dynamic Problems in Mechanics of Coupled Fields", by Roman Kushnir -- Damping of hydroelastic vibrations of the plate using shunted piezoelectric element. Part I: numerical model, by Sergey Lekomtsev, Dmitrii Oshmarin, Natalya Sevodina -- Damping of hydroelastic vibrations of the plate using shunted piezoelectric element. Part II: experiment, by Maksim Iurlov, Alexander Kamenskikh, Sergey Lekomtsev, Dmitrii Oshmarin -- Stationary dynamic acoustoelasticity problems of a thin plate in a perfect compress.
Keywords: Mechanics, Applied; Mechanics; Building materials; Engineering Mechanics; Classical Mechanics; Structural Materials